The contribution of problem-based learning in fostering an entrepreneurial attitude based on Pancasila values - Ernandia Pandikar; Idrus Affandi; Disman Disman; Dadang Sundawa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research is motivated by the problems of the Indonesian state in increasing Human Resources (HR) which aims to make people no longer depend on jobs provided by companies or business entities as a source of employment, but students learn to create jobs for themselves and even for others. So that with this, it is hoped that students will be able to shape themselves to have an entrepreneurial attitude based on the values of Pancasila. The purpose of this study is to describe the contribution of problem-based learning in fostering entrepreneurial attitudes based on Pancasila values. The research method used in this research is quantitative method. The results showed that Problem-Based Learning based on Pancasila values is effective in fostering entrepreneurial attitudes, this is evidenced by the results of the calculation of the r value of product moment correlation which means problem-based learning is closely related to entrepreneurial spirit. on Pancasila values and there is a significant influence of problem-based learning on entrepreneurial attitudes.